Land Use Conflicts in the Energy Transition: Dutch Dilemmas - Koelman, Mark; Hartmann, Thomas; Spit, Tejo (TeMA - Journal of Land Use, Mobility and Environment, 2018)
The transition from fossil to renewable energy needs changes in land use. The development of renewable energy sources introduce extra and sometimes new externalities, such as shadows and noise on landscape. There are governments who are experiencing difficulties when developing renewable energy sources especially when existing land owners (and others) start anticipating on those externalities. Therewith, land use conflicts have become a major issue for governments in meeting renewable energy policy objectives. This paper explores the way how three dilemmas: tiers of government dilemma, mode of governance dilemma and norm-setting dilemma are approached by public authorities using policy documents, interviews, literature research and examples of the Dutch energy transition.